Effect of different concentrations of colletotrichum gloeosporioides on disease development and disease severity on leaves of rubber tree (hevea brasiliensis) - Sangeetha a/p, Siva Sangu (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Disease development on leaves of rubber seedlings when inoculated with different inoculum concentrations of colletotrichum gloeosporioides were observed. The leaves used were manipulated in 16 ways in a combination of wounding and sterilizing the attached and detached leaves.